Authoritarian, But Not Nativist: Classifying Far-Right Parties in Latin America. - Borges, André; Zanotti, Lisa (Political Studies, 2025)
Research on far-right parties has mostly focused on Western Europe, where anti-immigration agendas and related nativist ideas have played a major role in right-wing radicalization. In this article, we analyze the rise of the far right in Latin America, a region where immigration has been much less prominent in public debates. Drawing on the 2020 Chapell Hill Expert Survey, we propose to assess the extent to which Latin American far-right parties fit existing conceptualizations that identify nativism and authoritarianism as the core characteristics of this party family. Given the relative unimportance of nativism as a distinguishing feature of cases of right-wing extremism/radicalism in the region, we propose a more parsimonious conceptualization of the far right. We also develop a typological classification and find that authoritarian-fundamentalist parties that embrace an extreme form of religious conservatism are the most common subtype of far-right party in Latin America.